EFFECT OF ARSENIC EXPOSURE ON METABOLIC ACTIVITIES INVOLVING ADAPTIVERESPONSES IN LIVER OF FRESH WATER FISHES (CHANNA PUNCTATA) - Haque, Md. Shahidul; Hossain, Md. Kamal; Roy, Swapan Kumar (Emirates Journal of Food and Agriculture, 2017)
As a major organ, liver plays the critical role in metabolic regulation, however, the metabolic activities are impaired by both environmental and chemical stimuli. Channa punctata variety of fishes was exposed to different concentration of sodium arsenate (Na2HAsO4) as the fishes are energetic and survive in the critical environment. Both 1 mM and 10 mM Na2HAsO4 enhanced protein content in liver for 1 h and 2 h, however, the effect was higher for 10 mM concentration. The fishes exposed to 100 mM Na2HAsO4 also causes increase in protein and the effect was lower than the previous doses. The inorganic phosphate (Pi) level was increased significantly whenever the fishes were exposed to Na2HAsO4 and found to be higher for 1 mM dose. The increased Pi release was also observed in response to higher dose, however, lower than the previous doses. Similar stimulatory effects on alkaline phosphatase activity were observed in liver exposed to the above concentrations and were found to be maximal for 1 mM dose. The results appear to indicate that the adaptive response involving the higher synthesis of molecules induced by arsenic is responsible for survive of the species and will give a new insight for the regulation of metabolic activities in liver and might be an index for characterization of the pathology of fishes.